Implementasi Metode Analytical Hierarchy Process untuk Menentukan Jenis Mobil Toyota - Mauludin, Muhammad Yunus; Kusdinar, Asep Budiman; Lelah , Lelah (LPPM UNIKA Santo Thomas, 2022)
The community's need for four-wheeled vehicles to help move from one place to another continues to grow rapidly. Everyone has different desires for the type of car they want to have. Different types of cars have different features. When it comes to owning a car, there are many factors to consider before buying a car and it can confuse a person about the various options available. This is the background behind the construction of a decision support system (DSS) for cars, namely the decision system to choose Toyota vehicles. The most obvious impact of the above environmental factors that can influence voters is ambiguity in car buying decisions. Based on these problems, a car purchase decision support system has been developed so that prospective car buyers can make decisions to choose a car more easily and quickly. The method used to build a decision support system is the Analytical Hierarchy Process (AHP).